2013
DOI: 10.3758/s13423-013-0457-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscientific information bias in metacomprehension: The effect of brain images on metacomprehension judgment of neuroscience research

Abstract: In the present study, we investigated how brain images affect metacomprehension judgments of neuroscience research. Participants made a prereading judgment of comprehension of the text topic and then read a text about neuroimaging findings. In Experiment 1, participants read text only or text accompanying brain images. In Experiment 2, participants read text accompanying bar graphs or text accompanying brain images. Then participants were asked to rate their comprehension of the text. Finally, they completed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
6
28
1
Order By: Relevance
“…Neuroimages have a strong psychological impact because of their concreteness and intuitive appeal. For a lay audience, studies have shown that neuroscience research is judged to be more scientifically credible [78] and more understandable [79] when it is accompanied by brain images rather than by bar graphs or more abstract topographical maps. Although other studies fail to replicate a general effect of neuroimagery on scientific persuasiveness [80,81], there appear to be at least some limited contexts [82] in which neuroimagery does add gravitas to scientific arguments.…”
Section: Discussionmentioning
confidence: 98%
“…Neuroimages have a strong psychological impact because of their concreteness and intuitive appeal. For a lay audience, studies have shown that neuroscience research is judged to be more scientifically credible [78] and more understandable [79] when it is accompanied by brain images rather than by bar graphs or more abstract topographical maps. Although other studies fail to replicate a general effect of neuroimagery on scientific persuasiveness [80,81], there appear to be at least some limited contexts [82] in which neuroimagery does add gravitas to scientific arguments.…”
Section: Discussionmentioning
confidence: 98%
“…Before we describe details of the present research, we first consider evidence from prior research that is relevant to students' metamemory knowledge about multimedia presentations. In this research, participants typically study a multimedia presentation (e.g., a text with static pictures) or a presentation with a single format (e.g., text alone), and then judge how well they have learned the target information in the text (e.g., Cardwell, Lindsay, Foerster, & Garry, ; Eitel, ; Ikeda, Kitagami, Takahashi, Hattori, & Ito, ; Serra & Dunlosky, ; Wiley, Sarmento, Griffin, & Hinze, ). The key outcome is whether judgments are higher for the multimedia presentation, which suggests the participants believe that the multimedia presentation is superior for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Across multiple experiments, the global judgments were higher for the multimedia presentation. Moreover, the multimedia presentation did not always boost actual test performance, so students judged multimedia presentations as superior even when they were inert (see also, Cardwell et al, ; Ikeda et al, ; for an exception, see Jaeger & Wiley, ). These results suggest the multimedia‐superiority hypothesis , which is simply that people believe that adding pictorial information to a lecture generally benefits memory.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, undergraduate students were shown mock scientific articles that were accompanied by brain images, a bar graph, or no visual display. The participants thought that the articles with the brain images displayed the best scientific reasoning (McCabe & Castel, 2008) and produced the highest ratings of scientific credibility (Ikeda, Kitagami, Takahashi, Hattori, & Ito, 2013). These results have been extended to the legal context given that participants that have taken part in mock jury trials were more likely to find a defendant not guilty by reason of insanity when neuroimages (that referenced the brain) were used to present their case (Gurley & Marcus, 2008).…”
mentioning
confidence: 74%
“…Similar studies have found that participants expressed greater self-reported comprehension on articles that were accompanied by brain images despite no significant differences in actual text comprehension (Ikeda et al, 2013). It has been suggested that reference to the brain may allow people to visualize components of a system that in turn leads to a greater belief that they can understand this system (Keil, 2006).…”
mentioning
confidence: 75%